2021
DOI: 10.1177/00139165211014629
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Weather on Assault

Abstract: This paper examines the role of local weather conditions in explaining variations in assault, in sub-tropical Brisbane, Australia. It details the extent to which local variations in weather are important in shaping the necessary preconditions for assault to take place. Results suggest that higher daily temperatures are associated with an increased propensity for assault at the neighborhood level after controlling for seasonal effects. Assaults occur significantly less frequently in summer than in spring and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 79 publications
1
16
0
Order By: Relevance
“…On the other hand, extreme temperatures were not a significant predictor of assault. After controlling seasonal variables, Corcoran and Zahnow (2021) found that higher daily temperatures are associated with an increased tendency for assault at the neighbourhood level. According to findings, climate change and human behaviour are closely linked to the quality of life.…”
Section: The Relationship Between Quality Of Life and Crime Based On ...mentioning
confidence: 97%
See 4 more Smart Citations
“…On the other hand, extreme temperatures were not a significant predictor of assault. After controlling seasonal variables, Corcoran and Zahnow (2021) found that higher daily temperatures are associated with an increased tendency for assault at the neighbourhood level. According to findings, climate change and human behaviour are closely linked to the quality of life.…”
Section: The Relationship Between Quality Of Life and Crime Based On ...mentioning
confidence: 97%
“…The quality of life has been classified into seven dimension; (a) environmental (Bracy et al, 2014;Mohit, 2013a;Mouratidis, 2021;Din et al, 2013); (b) physical (Bracy et al, 2014;Mohit, 2013a); (c) mobility (Bracy et al, 2014;Din et al, 2013); (d) social (Corcoran & Zahnow, 2021;Ghani, 2017a;Mohit, 2013a;Soh, 2012); (e) psychological (Corcoran & Zahnow, 2021;Kitchen & Williams, 2010;Lynch et al, 2020;Din et al, 2013;Trujillo & Howley, 2021); (f) economic (Ghani, 2017a;Din et al, 2013); (g) political (Ghani, 2017a;Mohit, 2013a;Din et al, 2013;Soh, 2012). Four out of seven dimension have been chosen to be applied in this study namely, (a) physical (Bracy et al, 2014;Mohit, 2013a); (b) psychological (Corcoran & Zahnow, 2021;Kitchen & Williams, 2010;Lynch et al, 2020;Serag El Din et al, 2013;Trujillo & Howley, 2021); (c) environment (Bracy et al, 2014;Mohit, 2013a;Mouratidis, 2021;Serag El Din et al, 2013); (d) social (Corcoran & Zahnow, 2021;Ghani, 2017a;Mohit, 2013a;Soh, 2012). To address the relationship between quality of life and crime based on weather changes, Figure 2 illustrate a conceptual framework domain related to crime and weather.…”
Section: Quality Of Lifementioning
confidence: 99%
See 3 more Smart Citations